1972
DOI: 10.2134/agronj1972.00021962006400040016x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Three Cutting Systems on the Yield, Water Use Efficiency, and Forage Quality of Sainfoin1

Abstract: Yield, water use efficiency, and forage quality of ‘Eski’ sainfoin (Onobrychis viciaefolia Scop.) were examined at the Central Great Plains Field Station, Akron, Colo. to determine its potential as a forage crop under dryland conditions. Despite below‐average rainfall during both years of the experiment, average seasonal forage yields over all treatments were 3,494 and 2,383 kg/ha dry matter for 1969 and 1970, respectively. Most of the forage yield was produced by the first cutting. Water use efficiency was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To study the effect of drought on acetone/water-extractable proanthocyanidin (PA) concentration and composition, we selected sainfoin (Onobrychis viciifolia Scop.) because it has good forage quality and higher proanthocyanidin concentrations than the other common proanthocyanidin-containing forage legumes birdsfoot trefoil (Lotus corniculatus) and white clover (Trifolium repens L.). , Also, there is some indication that sainfoin is drought-tolerant . Furthermore, several cultivars have been shown to contain an appropriate concentration and composition of PAs to reduce methane and nitrous oxide emissions from ruminant farming while maintaining high weight gains in ruminants. , Sainfoin was found to have high potential to be implemented in livestock systems to help improve their sustainability. , However, very little is known about how the proanthocyanidin concentration and structural characteristics of sainfoin are specifically affected by drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effect of drought on acetone/water-extractable proanthocyanidin (PA) concentration and composition, we selected sainfoin (Onobrychis viciifolia Scop.) because it has good forage quality and higher proanthocyanidin concentrations than the other common proanthocyanidin-containing forage legumes birdsfoot trefoil (Lotus corniculatus) and white clover (Trifolium repens L.). , Also, there is some indication that sainfoin is drought-tolerant . Furthermore, several cultivars have been shown to contain an appropriate concentration and composition of PAs to reduce methane and nitrous oxide emissions from ruminant farming while maintaining high weight gains in ruminants. , Sainfoin was found to have high potential to be implemented in livestock systems to help improve their sustainability. , However, very little is known about how the proanthocyanidin concentration and structural characteristics of sainfoin are specifically affected by drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Also, there is some indication that sainfoin is drought-tolerant. 18 Furthermore, several cultivars have been shown to contain an appropriate concentration and composition of PAs to reduce methane and nitrous oxide emissions from ruminant farming while maintaining high weight gains in ruminants. 6,19 Sainfoin was found to have high potential to be implemented in livestock systems to help improve their sustainability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to Hybner (2013), sainfoin performs better in areas or during years where most of the precipitation occurs in the spring and summer. Perhaps, the higher yields reported by Koch et al (1972), who had more precipitation in the spring and summer months during the study, could be due to the distribution of precipitation and/or genetic × environment interaction. The annual precipitation in 2013 (436 mm) was higher than in 2014 (385 mm); however, the forage DM was greater in 2014 (Table 3).…”
Section: Resultsmentioning
confidence: 92%
“…Koch et al (1972) reported forage DM as high as 3.49 Mg ha −1 for sainfoin cultivar Eski evaluated under rainfed conditions in Akron, CO, although the site has a semiarid climate as Sheridan, WY, and also received slightly higher amount of annual precipitation (377 mm) during the experimental years. More so, the large yield difference could not be attributed solely to cultivar because, Eski produced lower forage DM than Delaney, Remont, and Shoshone cultivars in a study by Hybner (2013).…”
Section: Resultsmentioning
confidence: 96%